Historieskrivning i kalenderform: Om Paul Ebers Calendarium Historicum - Lund, Rasmus Dalsgaard (Kirkehistoriske Samlinger, 2024)
Abstract In 1550, a historical calendar called Calendarium Historicum was published in Wittenberg by the Lutheran theologian Paul Eber. He was a close friend and colleague of the prominent reformer Phillip Melanchthon, and with the calendar he sought to supersede the catholic saints’ calendars by creating a Lutheran alternative. Calendars were not subjected to censorship in Denmark, and many copies of the calendar found their way to the Danish buyers, to whom the calendar presented Eber’s view of history. The content of the first edition of the calendar was centred around the deaths and births of German princes and admirable scholars from all over Christian Europe. It also commemorated the deeds of great men of ancient times, and, finally, the Holy Scriptures played a vital part. Popes, saints, and the Church Fathers, on the other hand, were omitted. With that being said, the content of the calendar was mostly apolitical and instead catered to the interests of humanists, regardless of their confession. In the following years, numerous editions of the calendar were published, and new historical events were continuously added. The last amended edition was published in 1579, and at that point, the character of the content had shifted. In the last edition of Calendarium Historicum, Lutheran self-awareness had become more pronounced, and the calendar now propagated what Mark A. Lotito has called, ”a Wittenberg view of the past”. The calendar still commemorated gifted scholars, but almost all the newly added ones were Protestants. Most of them were also German, and many were educated in Wittenberg. The last edition of the calendar also praised Lutheran kings and princes for their education and piety, while simultaneously highlighting the brutality and scrupulousness of the Protestants’ Catholic opponents, such as the Pope and the Holy Roman Emperor. Persecution of Protestants from all over Europe was memorialised, including that of people belonging to the Reformed confession. Thus, the calendar presented a Philippistic view of history, as Reformed theologians were also included, albeit not to the same degree as their Lutheran counterparts. Paul Eber also celebrated the proud history the Holy Roman Empire, as well as more contemporary victories against the French and the Ottomans. This article demonstrates the substantial evolution of the content of Calendarium Historicum from the first to the final edition, showing how the rising Lutheran selfawareness impacted Eber’s view of history. It is also shown that the copies that were owned in the Danish monarchy were closer the last edition than the first. Danish readers found their own history neglected and were confronted with the political, cultural, and theological superiority of the Germans and the Holy Roman Empire.